ANALYSIS OF THE POST-COVID NATIONAL ECONOMIC RECOVERY PROGRAM THROUGH MSMEs DEVELOPMENT - Rahmat Putra Ahmad Hasibuan (ASIAN PUBLISHER, 2022)
This study aims to analyze the condition of Indonesian economic and post-covid nastional economic recovery program through micro, small, medium enterprises (MSMEs) development during covid-19 in 2020-2021. This type of research is a qualitative descriptive analysis. This data collection method is obtained from secondary data by the relevan studies and literatures. From the results of data analysis, it can be concluded that MSMEs are able to encourage economic growth in Indonesia, by the shift from traditional marketing to digital marketing and assisted by government policy efforts.